The Role of Emotion Reactivity in Health Anxiety. (November 2017) - O'Bryan, Emily M.; McLeish, Alison C.; Johnson, Adrienne L.
Emotion reactivity, defined as heightened sensitivity, intensity, and persistence of emotional states, has been shown to contribute to the exacerbation of anxiety. However, the association between emotion reactivity and health anxiety has yet to be examined. The aim of the present investigation was to examine the unique predictive ability of emotion reactivity in terms of health anxiety in a sample of medically healthy undergraduates ( n = 194; 59.3% female, M age = 19.42, SD = 1.51, range = 18-26 years; 84.0% Caucasian). Findings indicated that, after controlling for the effects of gender, age, and anxiety sensitivity, greater emotion reactivity significantly predicted greater overall health anxiety (3.1% variance), as well as higher levels of affective (4.1% unique variance) and behavioral (4.8% unique variance) components. Findings suggest that experiencing emotions more frequently, intensely, and for longer durations of time prior to returning to baseline are associated with greater health preoccupations.